1989
DOI: 10.1038/jcbfm.1989.72
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Capillary Recruitment in the Brains of Awake Rats during Hypercapnia

Abstract: The present study investigates the question of whether increases in CBF induced by hypercapnia in awake rats are accompanied by increases in the number of perfused capillaries. For the detection of perfused capillaries, gamma-globulin-coupled fluorescein isothiocyanate was injected intravenously. In 10 brain structures the density of perfused capillaries per square millimeter was determined from coronal sections using a highly sensitive fluorescent microscopical method that, in contrast to others, avoided air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 21 publications
(10 reference statements)
1
49
0
Order By: Relevance
“…(3) The oxygen diffusibility (L) was assumed not to change at any measured blood flow level, because of the absence of capillary recruitment in human brain (Gobel et al, 1989;Kuschinsky and Paulson 1992;Vogel et al, 2004). At the highest oxygen extraction fraction compatible with normal oxygen consumption (E O2 E0.55, see Discussion), P mit O2 E0.…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The oxygen diffusibility (L) was assumed not to change at any measured blood flow level, because of the absence of capillary recruitment in human brain (Gobel et al, 1989;Kuschinsky and Paulson 1992;Vogel et al, 2004). At the highest oxygen extraction fraction compatible with normal oxygen consumption (E O2 E0.55, see Discussion), P mit O2 E0.…”
Section: Calculationsmentioning
confidence: 99%
“…The analysis revealed a physiological mitochondrial tension of 8.5 mm Hg, on assumption of constant oxygen diffusion conditions, including absent recruitment of capillaries. The absence is well supported for physiologic conditions, but it is unclear whether it extends to nonphysiologic states below the threshold of flowlimitation of oxygen consumption (Gobel et al, 1989, Kuschinsky andPaulson, 1992;Vogel et al, 2004).…”
Section: Effect Of Indomethacin On Cmr Omentioning
confidence: 99%
“…25 In brief, 125 Ci/kg body wt iodo [ 14 C]antipyrine (Biotrend) was infused with an increasing infusion rate for 1 minute. Parallel to this, 12 to 16 timed arterial blood samples were taken for the determination of the time course of the arterial iodo[ 14 C]antipyrine concentration.…”
Section: Autoradiographymentioning
confidence: 99%
“…In support of this suggestion, Gobel et al (1989) and Villringer et al (1991) also found that raising arte rial CO2 did not increase the number of plasma perfused or plasmatic capillaries, and Raichle et al (1976) reported that elevating the rate of blood flow by altering P aco2 did not enlarge the P S products of three BBB-permeable alcohols plus water.…”
Section: Capillary Recruitment Hypothesismentioning
confidence: 89%